Domination Of Islamic Fiqih Doctrine On Positive Law Concerning Divorce Maqashid Sharia Perspective - Nurdalia Bate; Muammar Muhammad Bakry; Abd. Rauf Muhammad Amin; Rahmawati, Rahmawati; Hannani, Hannani; Kurniati, Kurniati; Abd. Karim Faiz (International Journal of Education, Vocational and Social Science, 2024)
Divorce is the breaking of the marriage bond due to a problem in the household. In its application, especially in the city of Parepare, there is still a polemic regarding the understanding between the determination of talaq. Therefore, the authors are interested in researching and examining how the provisions of divorce in the fiqh of Imam Shafi'i and the positive law applicable in Indonesia and the dominance of Islamic fiqh doctrine on positive law regarding the fall of divorce using the Maqashid Sharia perspective. The purpose of this study aims to describe the regulation of divorce and to analyse the dominance of Islamic fiqh doctrine on positive law in the study of the perceptions of religious figures in Parepare city about the occurrence of divorce from the perspective of Maqashid Sharia. The method used by the authors in this research is based on the field reserch method. The results of this study indicate that divorce according to positive law in Indonesia dominates the validity of talaq determination due to the guidance of KHI and applicable laws.